Role of Magnesium Sulphate as Tocolysis in Preterm Labour - Fazila (Indus Journal of Bioscience Research, 2025)
Background: Preterm labour is a major cause of neonatal morbidity and mortality worldwide. Magnesium sulphate is commonly used as a tocolytic agent due to its ability to reduce uterine contractions and provide fetal neuroprotection. Objective: To assess the role of magnesium sulphate as a tocolytic in preterm labour, focusing on its effectiveness in reducing uterine contractions and delaying delivery beyond 48 hours. Methodology: This descriptive study was conducted at the Obstetrics and Gynecology Department, Shaikh Zaid Women Hospital, Larkana, enrolling 100 females aged 18–40 years with parity ≤5 and gestational age >28 weeks presenting with preterm labour. Participants received a loading dose of 4 grams of magnesium sulphate intravenously, followed by a maintenance infusion of 1.0–2.0 grams per hour, titrated according to uterine activity. Results: The mean age of participants was 28.6 ± 5.1 years, with a mean gestational age of 31.2 ± 1.9 weeks. Reduction in uterine contractions was observed in 67% of patients, while 62% achieved a delay in delivery beyond 48 hours. Stratification showed a statistically significant association between BMI and reduction in uterine contractions (p = 0.04), whereas no significant association was observed with other variables. Conclusion: Magnesium sulphate effectively reduces uterine contractions and delays delivery beyond 48 hours in a significant proportion of patients with preterm labour. Its role as both a tocolytic and a fetal neuroprotective agent supports its continued use in clinical practice, especially in settings with limited resources.